Вибір технології зшивання ізоляції для кабелів на напругу понад 6 кВ - Золотарьов, Володимир Михайлович; Антонець, Тарас Юрійович; Гонтар, Юлія Григорівна; Антонець, Станіслав Юрійович (Національний технічний університет "Харківський політехнічний інститут", 2025)
У статті розглянуто питання вибору оптимальної технології зшивання ізоляції силових кабелів із зшитого поліетилену на напругу понад 6 кВ, що є критично важливим аспектом проєктування та експлуатації кабельних ліній середньої, високої та надвисокої напруги. Проведено детальний аналіз двох промислових методів – пероксидного та силанольного зшивання поліетилену. Показано, що хоча обидві технології формують тривимірну зшиту структуру, їхня молекулярна природа, механізми хімічних реакцій, рівномірність зшивки, енергія міжмолекулярних зв’язків і термічна стабільність принципово відрізняються. Особливу увагу приділено порівнянню структурних формул і характеристик матеріалів, зокрема енергії зв’язків, ступеня зшивки, кількості макромолекул у вузлах зшивки та впливу побічних продуктів на однорідність ізоляції. Проаналізовано міжнародний досвід використання кабелів із зшитого поліетилену, включно з вимогами європейських енергетичних компаній та результатами багаторічної експлуатації. Наведені дані показують, що силанольна зшивка не забезпечує необхідної довговічності та стійкості ізоляції при напругах понад 6–10 кВ, що підтверджується випадками масових відмов у різних країнах, зокрема й в Україні. Розкрито причини прискореного старіння силанольної ізоляції, пов’язані з проникненням вологи, нерівномірністю зшивки та виникненням водних і електричних триінгів. Окремо підкреслено важливість комплексних електричних випробувань кабелів із зшитого поліетилену, зокрема контролю часткових розрядів із чутливістю 0,5 пКл, наявності ресурсних випробувань за HD 620 та сертифікації у незалежних лабораторіях. Узагальнивши результати численних досліджень і світового досвіду, автор робить висновок про беззаперечну перевагу пероксидної технології зшивання для кабелів напругою понад 6 кВ і необхідність закріплення цієї вимоги в національних нормативних документах України.

This article examines the problem of selecting the optimal insulation crosslinking technology for medium-, high-, and extra-high-voltage Cross-Linked Polyethylene power cables operating above 6 kV. Two industrial methods of polyethylene crosslinking–peroxide and silane–are analyzed in detail. Although both approaches produce a three-dimensional polymer network, their chemical nature, reaction mechanisms, homogeneity of crosslinking, bond energy, and long-term stability differ fundamentally. The study emphasizes the comparison of structural formulas and material properties, including crosslink density, degree of crosslinking, number of macromolecules involved in a crosslink node, and the influence of by-products that affect insulation homogeneity. The article highlights extensive international experience regarding the performance of Cross-Linked Polyethylene cables manufactured using different technologies. Technical requirements of major European utility companies and decades of operational practice clearly indicate that silane-crosslinked polyethylene does not provide sufficient long-term reliability for cables above 6–10 kV. Documented field failures–caused by moisture ingress, uneven crosslinking, and the formation of electrical and water treeing–demonstrate the inability of silane insulation to ensure stable performance under medium-voltage conditions. Evidence from Ukrainian installations further supports these conclusions. Special attention is paid to the role of factory testing as an essential component of cable production. High-voltage test systems with partial discharge sensitivity down to 0.5 pC, as well as long-term ageing tests performed in accordance with HD 620, are identified as mandatory requirements for ensuring insulation quality and lifetime. Based on comprehensive analytical results, laboratory studies, and decades of global operating experience, the article concludes that peroxide crosslinking technology remains the only reliable and recommended method for manufacturing Cross-Linked Polyethylene insulation for cables rated above 6 kV. The author stresses the necessity of incorporating this requirement into national Ukrainian regulatory documents to ensure the reliability and safety of power networks.
Selection of insulation crosslinking technology for cables rated above 6 kV
Keywords: зшитий поліетилен; пероксидне зшивання; силанольна технологія; часткові розряди; ресурс кабелю; середня напруга; XLPE insulation; peroxide crosslinking; silane technology; partial discharges; cable lifetime; medium voltage